Bridging views in cinema: a review of the art and science of view integration. Issue 5 (6th March 2017) - Levin, Daniel T.; Baker, Lewis J.
Abstract : Recently, there has been a surge of interest in the relationship between film and cognitive science. This is reflected in a new science of cinema that can help us both to understand this art form, and to produce new insights about cognition and perception. In this review, we begin by describing how the initial development of cinema involved close observation of audience response. This allowed filmmakers to develop an informal theory of visual cognition that helped them to isolate and creatively recombine fundamental elements of visual experience. We review research exploring naturalistic forms of visual perception and cognition that have opened the door to a productive convergence between the dynamic visual art of cinema and science of visual cognition that can enrich both. In particular, we discuss how parallel understandings of view integration in cinema and in cognitive science have been converging to support a new understanding of meaningful visual experience. WIREs Cogn Sci 2017, 8:e1436. doi: 10.1002/wcs.1436 This article is categorized under: Psychology > Attention Psychology > Perception and Psychophysics Neuroscience > Cognition Abstract : The art of cinema and the science of vision converge in this research review. When assembling a series of shots into a coherent sequence, filmmakers have discovered a set of principles that help distinguish effective edits from jarring ones. These principles can be mined by cognitive science to help understand real‐world view integration and event perception.